The cost of treatment failure: resource use and costs incurred by hepatitis C virus genotype 1–infected patients who do or do not achieve sustained virological response to therapy. Issue 3 (1st August 2013) - Backx, M.; Lewszuk, A.; White, J. R.; Cole, J.; Sreedharan, A.; van, S.; Diels, J.; Lawson, A.; Neal, K. R.; Wiselka, M. J.; Ito, T.; Irving, W. L.
Summary Chronic hepatitis C virus (HCV) infection places a considerable economic burden on health services. Cost‐effectiveness analyses of antiviral treatment for patients with chronic HCV infection are dependent on assumptions about cost reductions following sustained virological response (SVR) to therapy. This study quantified the medium‐term difference in health resource usage and costs depending on treatment outcome. Retrospective chart review of patients with HCV genotype 1 infection who had received at least 2 months pegylated interferon and ribavirin therapy, with known treatment outcome was conducted. Disease status was categorized as chronic hepatitis, cirrhosis or decompensated liver disease. Health resource use was documented for each patient in each disease state. Unit costs were from the NHS 'Payment by Results' database and the British National Formulary. One hundred and ninety three patients (108 SVR, 85 non‐SVR) with mean follow‐up of 3.5 (SVR) and 4.9 (non‐SVR) years were enrolled. No SVR patient progressed to a more severe liver disease state. Annual transition rates for non‐SVR patients were 7.4% (chronic hepatitis to cirrhosis) and 4.9% (cirrhosis to decompensated liver disease). By extrapolation of modelled data over a 5‐year post‐treatment period, failure of patients with chronic hepatitis to achieve SVR was associated with a 13‐fold increase (roughly £2300) in costs, whilst for patients who were retreated, the increase was 56‐fold, equating to more than £10 000. Achievement of an SVR has significant effects on health service usage and costs. This work provides real‐life data for future cost‐effectiveness analyses related to the treatment for chronic HCV infection.